Effects of different feeding levels during three short periods of gestation on gilt and litter performance, nutrient digestibility, and energy homeostasis in gilts. Issue 3 (1st March 2017) - Ren, P.; Yang, X. J.; Cui, S. Q.; Kim, J. S.; Menon, D.; Baidoo, S. K.
Abstract: The present study investigated the effects of different feeding levels during 3 short periods of gestation on gilt and litter performance, apparent total tract digestibility (ATTD) of energy and nutrients, and energy homeostasis in gilts. A total of 18 gilts were allotted to 1 of 3 dietary treatments using a completely randomized design. All gilts were fed 1 common corn-soybean meal-based diet with the amount of 1.0 · maintenance energy intake (100 · BW (BW) 0.75 kcal ME/d) throughout gestation except 3 periods of 7 d when dietary treatments were imposed on d 27, d 55, and d 83 of gestation. During the 3 short periods, gilts were fed 1 of 3 different feeding levels: 0.5, 1.0, and 2.0 · maintenance energy level (0.5M, 1.0M, and 2.0M, respectively). Results showed that gilts on 2.0M feeding level had higher ( P < 0.05) weight gain from d 27 to 109 of gestation (37.05 vs. 15.34 kg) and greater ( P < 0.05) BW change, average daily gain, and gain to feed ratio during gestation periods 1 (d 27–34) and 3 (d 83–90) when compared with gilts on 0.5M feeding level. No differences ( P > 0.10) in litter performance were observed among the 3 feeding levels. Additionally, the slopes of BW change in response to feeding levels in period 1 were 4.32 kg/0.5M change from 0.5M to 1.0M feeding level and 3.72 kg/0.5M change from 1.0M to 2.0M feeding level, respectively. There were quadratic ( P < 0.05) effects of feeding levels on ATTD of dry matter and gross energy during periods 1 and 2 (d 55–62). Furthermore, fasting plasma concentrations of acyl ghrelin and nonesterified fatty acid (NEFA) in period 1 were greater ( P < 0.01) in gilts on 0.5M feeding level than those on 2.0M feeding level. In conclusion, increasing feeding levels during 3 short periods increased primiparous sow performance during these short periods but did not affect litter performance. ATTD of energy and nutrients, and BW change efficiency were maximized for gilts on 1.0 M feeding level. The data also indicated that sows on the lowest feeding level were exposed to negative energy balance as evidenced by the higher plasma acyl ghrelin and NEFA concentrations.